Infiltration of Small Arms and Light Weapons into Benue Valley and Its Impact on the Conflict Between Pastoralists and Farmers - Paulina Ada Akpa; Terver Akpar; Samson Aondowase Fada (International Studies Journal)
One of the challenges confronting nation states is the proliferation of small arms and light weapons. This problem is more pronounce in developing countries where there are porous borders and weak institutions responsible for border security like Nigeria. The proliferation and misuse of small arms and light weapons in the country is progressively complex and multifaceted phenomenon that affects people and insecurity. This paper examined the infiltration of small arms and light weapons into Benue Valley and its impact on the conflict between pastoralists and farmers. Descriptive research design was adopted while the data for the study was generated from interviews and questionnaire instruments. State fragility theory provided framework for the study. Findings from the study revealed that the availability of illegal small arms and light weapons in the Benue valley has greatly aggravated farmers and herders conflict. The destabilizing accumulation and uncontrolled spread of small arms and light weapons by Fulani herders and farmers has increased the intensity and duration of conflict, undermines the sustainability of peace agreements, impedes the success of peace building, frustrates efforts aimed at the prevention of the conflict and hinders considerably the provision of humanitarian assistance in the affected areas. The study therefore recommends that: there is also need for an improved border management mechanism using modern and sophisticated detection equipment to discourage arms trafficking through the borders.